The art of the impossible politics as morality in practice ; speeches and writings, 1990 - 1996 - Havel, Václav 1936-2011 (Knopf, 1997)
This volume consists of thirty-five of these essays, written between the years 1990 and 1996, that manage to be both profoundly personal and profoundly political. Havel writes of totalitarianism, its miseries and the nonetheless difficult emergence from it. He describes how his country and the other post-communist countries are learning democracy from scratch and are encountering obstacles from inside and out. He marvels at the single technology-driven civilization that envelops the globe, and the challenges this presents to multicultural realities. And he reminds us that - contrary to all appearances - common sense, moderation, responsibility, good taste, feeling, instinct, and conscience are not alien to politics, but are the very key to its long-term success
Aus dem Tschech. übers.
Keywords: Democratisering; Ethische aspecten; Morale politique; Politiek; Ethik; Politik; Citizenship -- Moral and ethical aspects; Civilization, Modern -- 1950- -- Moral and ethical aspects; Political ethics; Post-communism; Responsibility; Truth; Politische Ethik; Tschechische Republik; Czech Republic -- Politics and government -- Moral and ethical aspects; Tschechien; Aufsatzsammlung